Artifacts in T1ρ-Weighted Imaging: Compensation for B(1) and B(0) Field Imperfections - Witschey, Walter R.T. (2007)
The origin of spin locking image artifacts in the presence of B(0) and B(1) magnetic field imperfections is shown theoretically using the Bloch equations and experimentally at low (ω(1) ≪ Δω(0)), intermediate (ω(1) ~ Δω(0)) and high (ω(1) ≫ Δω(0)) spin locking field strengths. At low spin locking fields, the magnetization is shown to oscillate about an effective field in the rotating frame causing signature banding artifacts in the image. At high spin lock fields, the effect of the resonance offset Δω(0) is quenched, but imperfections in the flip angle cause oscillations about the ω(1) field. A new pulse sequence is presented that consists of an integrated spin echo and spin lock experiment followed by magnetization storage along the -z-axis. It is shown that this sequence almost entirely eliminates banding artifacts from both types of field inhomogeneities at all spin locking field strengths. The sequence was used to obtain artifact free images of agarose in inhomogeneous B(0) and B(1) fields, off-resonance spins in fat and in vivo human brain images at 3T. The new pulse sequence can be used to probe very low frequency (0–400 Hz) dynamic and static interactions in tissues without contaminating B(0) and B(1) field artifacts.